Intestinal Parasitic Infections Among Pregnant Women in Venezuela - Alfonso J. Rodríguez-Morales; Rosa A. Barbella; Cynthia Case; Melissa Arria; Marisela Ravelo; Henry Perez; Oscar Urdaneta; Gloria Gervasio; Nestor Rubio; Andrea Maldonado; Ymora Aguilera; Anna Viloria; et al. (Hindawi Limited, 2006)
Introduction. Intestinal parasitic infections, especially due to helminths, increase anemia in pregnant women. The results of this are low pregnancy weight gain and IUGR, followed by LBW, with its associated greater risks of infection and higher perinatal mortality rates. For these reasons, in the setting of no large previous studies in Venezuela about this problem, a national multicentric study was conducted. Methods. Pregnant women from nine states were studied, a prenatal evaluation with a coproparasitological study. Univariated and multivariated analyses were made to determine risk factors for intestinal parasitosis and related anemia. Results. During 19 months, 1038 pregnant women were included and evaluated. Intestinal parasitosis was evidenced in 73.9%: A lumbricoides 57.0%, T trichiura 36.0%, G lamblia 14.1%, E hystolitica 12.0%, N americanus 8.1%, E vermicularis 6.3%, S stercoralis 3.3%. Relative risk for anemia in those women with intestinal parasitosis was 2.56 (P<.01). Discussion. Intestinal parasitoses could be associated with conditions for development of anemia at pregnancy. These features reflect the need of routine coproparasitological study among pregnant women in rural and endemic zones for intestinal parasites. Further therapeutic and prophylactic protocols are needed. Additional research on pregnant intestinal parasitic infection impact on newborn health is also considered.